Sustainability assessment of timber bridge design - An iterative study of a conceptual timber bridge design using life cycle and Life Cycle Costing Assessment - Holmström, Olivia; Högberg, Anna (My University, 2025)
Today, the building and infrastructure sector is a significant contributor to global green house gas emissions, with bridges often designed using materials with high embodied carbon, such as steel and concrete. Timber bridges present a renewable, carbon-storing alternative that can significantly reduce environmental impact. However, the demand remains low due to negative perceptions about durability and maintenance. This thesis aims to compare the environmental and economic performance of timber and steel components in bridge design, identifying key factors that influence sustainability and cost across the entire life cycle. Developed with Timber Bridges Specialist AB, the project follows an early-stage design process for an ongoing project using its context as a framework. The work was carried out using FEM-Design, where the bridge was structurally modeled and dimensioned, followed by iterative Life Cycle Assessment (LCA) and Life Cycle Cost Assessment (LCCA) to evaluate alternative deck and railing configurations. The study also assessed the substitution of pressure-impregnated timber with heat-treated timber to explore potential sustainability improvement. The results show that timber components, particularly in railings, significantly lower climate impact and cost compared to steel. Efficient use of steel, such as trapezoidal corrugated sheets, can be a good alternative due to its efficient material use. Overall, timber outperforms steel both when it comes to environmental impact and cost, especially when carbon storage is considered. The findings emphasize that optimizing material selection and material efficiency for each bridge component can improve sustainability and cost-effectiveness, promoting broader adoption of timber bridges in future projects.
Keywords: Timber bridge; Structural design; LCA; LCCA; FEM-Design; Sustainability